The economic structure of towns in Ireland - O’Donoghue, Cathal; Geoghegan, Cathal; Heanue, Kevin; Meredith, David (Statistical and Social Inquiry Society of Ireland, 2014)
In this paper we undertook an analysis of the Economic Structure of Towns in Ireland, classified by size. While economic development in Ireland is often viewed as an East-West issue, the situation is more complex. Traditionally towns were regarded as having poor demographics, while our analysis indicates that towns have experienced net inward migration and although they have a higher dependency ratio than cities, it is due to more children. However towns exhibit lower skill levels on average and a greater reliance on low growth sectors. In particular, towns have had the highest impact in terms of changed unemployment as a result of the economic downturn. This is particularly manifested via one third of working age households having no one at work and with a higher poverty rate than the national average. This has had a greater impact on savings during the crisis than the national average, with consequential impacts on domestic demand. Smaller towns on average are more likely to have a higher share of employment rather than jobs as a result of commuting to larger growth centres. We developed an indicator known as economic strength that combines unemployment with migration. Larger towns were weaker in terms of this index. Also there was a significant spatial spread. The weakest towns were more likely to be the local growth centre for more depressed regions, be more peripheral, and have lower skills. We concluded by recommended a targeted policy programme to make towns more attractive to live in and visit; to make it easier to do business; to increase consumer demand and sentiment; and, to improve access to finance of SMEs.
Keywords: local economic development; small and medium towns; 314.15